IMPLEMENTASI PERATURAN PEMBUANGAN SAMPAH LAUT OLEH KAPAL TANKER DARI PERSPEKTIF HUKUM LINGKUNGAN INDONESIA - Semuel Dumak Parerungan (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pelayaran Malahayati, 2022)
The state wants the protection of the marine environment through the ratification of various international conventions such as the International Convention for the Prevention of Pollution from the Ship (hereinafter referred to as MARPOL). ), which regulates the port authority, in this case the role of the harbormaster in upholding the sea due to oil pollution by tankers as stipulated in the 1982 Marine Law which stipulates that law enforcement against perpetrators of marine environmental pollution must be carried out. out by flag states (flag countries), port states and coastal states as stipulated by Articles 213-220 of the 1982 Law of the Sea Convention. Marine pollution can also be the result of ship operations and or ship accidents, whether intentional or unintentional, however due to pollution The sea has a very broad impact on all life both in the sea and on land that is affected by pollution. The research method used is qualitative. Data collection techniques using interviews, observation and literature review. Data validity using triangulation. The data analysis technique uses an interactive model of qualitative analysis. The conclusion of this study, Indonesian positive law, the law aims to avoid oil pollution in the sea by tankers through the implementation of oil disposal management by tankers and monitoring the completeness of ship infrastructure. to the standardization of pollution owned by tankers. Prevention efforts are being made to tackle oil pollution at sea by tankers through a pollution prevention monitoring mechanism with pollution control equipment to prevent and control pollution for tankers entering the territory of the Republic of Indonesia, if tankers cannot anticipate pollution, Syahbandar and the team formed will tackle the pollution through facilities owned by oil companies.